MENENTUKAN BATAS NEGARA GUNA MENINGKATKAN PENGAWASAN, PENEGAKAN HUKUM, DAN KEDAULATAN NKRI - Djalal, Hasjim (Indonesia Defense University, 2013)
In order to assure the control and the law enforcement as well as the sovereignty of a state in a border area, they will have first of all determine the borderline of the states, preferably with the neighboring states as the case maybe. Indonesia is very conscious of determining its borders with its neighbors, either on land or at sea and in the air, as well as in the seabed area (continental shelf) beyond its territorial sovereignty. Therefore, it has to determine a number of maritime borders with different rights and obligations, such as internal waters, archipelagic waters, territorial sea, contiguous zones, economic zones, and continental shelf/margin. In addition, in view of its strategic location, it has also to determine the location or the archipelagic sea lanes in order foreign vessels to be able to exercise the right of archipelagic sea lanes passage in addition to the right of innocent passage. Moreover, being an archipelagic state with a very large and intensive process of decentralization, Indonesia also has to deal with the problems of boundaries between the various provinces in the country either maritime or land boundaries.Â Keywords: maritime boundaries, agreements with neighboring states, different kind of maritime boundaries.